PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR ASPEK PENGETAHUAN PADA MATERI HIDROLISIS-BUFFER - Varantika, Novanda; Susatyo, Eko Budi; Sumarni, Woro (Chemistry in Education, 2018)
Abstract This study aims to determine the magnitude of the influence of group guided inquiry on cognitive aspects of learning outcomes. The study used pretest-posttest control group design, while the sampling technique is cluster random sampling. In this research. Students at XI IPA 4 have been decided as experiment class and XI IPA 6 as control class. Data taken using objective tests with reasoning. Data obtained, analyzed by using t test and determination coefficient. Based on t-test, it is found that tcount of cognitive aspects of learning outcomes is 2,015 is bigger than tcritic is 2,00, meaning there is significant difference between mean of cognitive aspects of learning outcomes of experiment class and control class. Based on the analysis of determination coefficient obtained that study guided inquiry influence on cognitive aspects of learning outcomes of 9,00%. Based on the result of the research, it can be concluded that the study of group investigation has an effect on cognitive aspects of learning outcomes is 9,00%. Keywords: Guided Inquiry, Cognitive Aspects, Hydrolisis-buffer material.